Environmental Disclosure Quality and its Impact on the Value of Indonesian Public Companies - Rahayu Nugraheni; Olivia Sindi Sapan (Universitas Sains dan Teknologi Komputer, 2026)
This study examines the effect of environmental disclosure quality on the value of Indonesian publicly listed companies. The research applies an explanatory quantitative approach using panel data obtained from annual reports, sustainability reports, and stock market information of non-financial companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The final sample consists of 42 companies with 168 firm-year observations from manufacturing, mining, and energy sectors. Environmental disclosure quality is measured using a content analysis index based on information depth, quantitative disclosure, and reporting consistency, while firm value is proxied by Tobin’s Q and analyzed using a fixed effect panel regression model. The findings indicate that environmental disclosure quality has a positive and significant effect on firm value, suggesting that investors perceive transparent environmental reporting as a credible signal of corporate sustainability and lower information asymmetry. This study contributes by developing a substance-based environmental disclosure measurement framework aligned with recent sustainability reporting regulations in Indonesia.